2021
DOI: 10.1080/21655979.2021.2008639
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Pvt1 oncogene (CircPVT1) promotes the progression of papillary thyroid carcinoma by activating the Wnt/β-catenin signaling pathway and modulating the ratio of microRNA-195 (miR-195) to vascular endothelial growth factor A (VEGFA) expression

Abstract: Circular RNAs (circRNAs) have been reported to be involved in the progression of papillary thyroid carcinoma (PTC). However, the role of circular RNA Pvt1 oncogene ( circPVT1) in PTC has rarely been reported. In this study, we aimed to investigate the function and mechanism of circPVT1 in PTC. The expression level of circPVT1, miR-195 and VEGFA were determined by reverse transcription‑quantitative PCR (RT‑qPCR). Fisher’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 75 publications
0
29
0
Order By: Relevance
“…Subsequently, the cells were fixed in 4% paraformaldehyde and stained with DAPI. Finally, cell counting was performed using fluorescence microscopy to quantify the percentage of EdU-positive cells [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the cells were fixed in 4% paraformaldehyde and stained with DAPI. Finally, cell counting was performed using fluorescence microscopy to quantify the percentage of EdU-positive cells [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also revealed that different circRNAs contain the same type and miRNA binding sites that can specifically bind to miRNAs, thereby reducing miRNA activity and upregulating the expression of miRNA-related target genes (Shu et al, 2020;Luo et al, 2021), such as hsa_circ_0058124 and circUBAP2, which are revealed as miR-370-3p sponges and promote proliferation and invasion of TC cells (Liu L. et al, 2020;Xiong et al, 2021b). In addition, specific circRNAs protect homologous mRNAs from miRNA-mediated degradation by inhibiting miRNA activity (Zeng et al, 2021). For example, Zeng et al revealed that circPVT1 serves as a ceRNA to sequester miR-195 and promote the PVT1-mediated malignant progression in PTC (Zeng et al, 2021).…”
Section: Biological Functions Of Circrnas In Tc Oncogenic Activity Of...mentioning
confidence: 99%
“…In addition, specific circRNAs protect homologous mRNAs from miRNA-mediated degradation by inhibiting miRNA activity (Zeng et al, 2021). For example, Zeng et al revealed that circPVT1 serves as a ceRNA to sequester miR-195 and promote the PVT1-mediated malignant progression in PTC (Zeng et al, 2021). Accumulating evidence has identified individual circRNAs containing multiple RBP motifs, suggesting circRNAs may sponging protein and modulate RBP-dependent functions (Bronisz et al, 2020;Tsitsipatis et al, 2021).…”
Section: Biological Functions Of Circrnas In Tc Oncogenic Activity Of...mentioning
confidence: 99%
“… Diagnosis 60 patients 3 cell lines China 2016 Wang [ 86 ] miR-195 VEGFA CircPVT1 promoted the PTC cell migration by miR-195 sponging and subsequent VEGFA up regulation. Diagnosis 50 patients 4 cell lines China 2021 Zeng [ 87 ] miR-520a-3p JAK1 MiR-520a-3p inhibited the JAK-STAT signaling by JAK1 suppression which inhibited EMT and migration of PTC cells. Diagnosis 137 patients 6 cell lines China 2019 Bi [ 88 ] miR-361-5p ROCK1 MiR-361-5p inhibited PTC cells migration by ROCK1 targeting.…”
Section: Introductionmentioning
confidence: 99%
“…VEGFA is a tyrosine kinase receptor involved in angiogenesis. CircPVT1 promoted the PTC cell migration by miR-195 sponging and subsequent VEGFA up regulation [ 87 ]. Janus kinases (JAK) are a class of tyrosine kinases involved in cell growth, differentiation, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%